Pengaruh Electronic Word of Mouth (E-Wom) dan Citra Merek terhadap Keputusan Pembelian Konsumen di Bakpia Djava Yogyakarta - Anggun Nur Ariani; Nurul Hidayah; Safira Nuraisyah; Ginting Cindy Perbina; Azka Hayuna Widyadana; Alief Misbach Romadhoni; Tiara Eka Pertiwi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to evaluate the influence of Electronic Word of Mouth and brand image on consumer purchase decision at Bakpia Djava Yogyakarta. Quantitative descriptive research method is used to conduct this research. Primary data was gathered from 64 respondents who have bought Bakpia Djava products before using survey method by distributing questionnaires. The data was analyzed by using IBM SPSS through validity and reliability test, classical assumption test, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The result shows that Electronic Word of Mouth has a positive and significant effect on purchase decision (β = 0.246; p = 0.007), and brand image also has a positive and significant effect (β = 0.729; p < 0.001). On the other hand, Electronic Word of Mouth and Brand Image also have a substantial impact on consumer purchasing decisions (F = 50.361; p < 0.001) where the coefficient of determination (R²) is 0.623. This implies that 62.3% of the variations in the consumer's purchasing decisions are accounted for by these two variables. This study supports the marketing strategies used by firms such as building a brand image and encouraging Electronic Word of Mouth that leads to an increase in the consumer’s purchasing decisions. In this way, the study adds value to the consumer behavior literature by demonstrating the application of the Theory of Planned Behavior in predicting purchasing decisions.